SIMULASI FILTER SALLEN KEY DENGAN SOFTWARE PSPICE - Prawiroredjo, Kiki (Jurnal Teknik Elektro, 2007)
A SallenâKey filter is a type of active filter, particularly valued for its simplicity. The circuitproduces a 2-pole (12 dB/octave) lowpass or highpass response using two resistors, twocapacitors and a buffer amplifier or operational amplifier. By varying the gain of theamplifier the filter will have a certain type of frequency response such as Bessel, Butterworthor Chebyshev. Higher-order filters can be obtained by cascading two or more stages. Thisfilter topology is also known as a voltage controlled voltage source (VCVS) filter. The opampprovides buffering between filter stages, so that each stage can be designedindependently. PSpice software can be used to simulate the filter circuits and the frequencyresponse can be analyzed before the circuits are built. Designers can change the frequencyresponse easily by changing the values of the components in the filter design by PSpicesoftware. The results of the simulation show that the Bessel response has the lowest outputvoltage and the lowest roll-off, Butterworth frequency response has higher output voltagethan Bessel and as the most stable one but Chebyshev response has the highest outputvoltage and the highest roll-off but not stable.Keywords: Sallen-Key filter, PSpice software, frequency response, lowpass filter, highpassfilter, Operational Amplifier, Bessel, Butterworth, Chebyshev.